Effects of ultrasonic treatment on removal of abundant proteins and enrichment of low-abundance proteins in defatted soybean meal by isopropanol - Mingmei Liu; Guoqi Zhao; Bin Qi; Jinshun Zhan (Biotechnology & Biotechnological Equipment, 2016)
The establishment of a method for the removal of abundant proteins (APs) and enrichment of low-abundance proteins (LAPs) might contribute to further studies on the physiological functions of LAPs in animals and humans without the influence of APs. The aim of our study was to investigate the effect of ultrasonic treatment on the removal of APs and enrichment of LAPs in defatted soybean meal using isopropanol. The optimal isopropanol concentration for the removal APs was initially shown to be 50% without ultrasonic treatment. The highest protein concentration was achieved at 50% isopropanol concentration with 1 h of total extraction time (ultrasonic treatment and water-bath vibrating) and when the sample was treated with ultrasound at 400 W for 10 min. Under these conditions, the protein concentration increased by 26.42% when compared to the control (no ultrasonic treatment). Furthermore, no β-conglycinin and glycinin was detected by sodium dodecyl sulphate–polyacrylamide gel electrophoresis and mass spectrometry.